2007
DOI: 10.1007/s00134-007-0745-5
|View full text |Cite
|
Sign up to set email alerts
|

Replacement of 24-h creatinine clearance by 2-h creatinine clearance in intensive care unit patients: a single-center study

Abstract: In intensive care patients, 24-h CrCl results in a large proportion of non-valid determinations, even under conditions of close monitoring. Two-hour CrCl is an adequate substitute, even in patients who are unstable or who have irregular diuresis where a 24-h collection is impossible. The Cockroft-Gault equation seems less useful in this setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
55
0
6

Year Published

2008
2008
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(64 citation statements)
references
References 30 publications
3
55
0
6
Order By: Relevance
“…Conversely, in patients with a long history of hospital admission (Ͼ1 month), CL Cr estimates may lead to the overestimation of renal function, so that the direct measurement of CL Cr should be performed to accurately assess the glomerular filtration rate and to prevent vancomycin overexposure. An inaccuracy of CL Cr estimates was encountered whenever the daily output of creatinine from muscles is impaired by the degree of muscle loss which may occur when a patient is bedridden for a long time (9,11). Another limitation may be represented by the fact that these nomograms are not valid for functionally anephric patients on dialysis and perhaps also for patients with very low CL Cr estimates of Ͻ10 ml/min.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, in patients with a long history of hospital admission (Ͼ1 month), CL Cr estimates may lead to the overestimation of renal function, so that the direct measurement of CL Cr should be performed to accurately assess the glomerular filtration rate and to prevent vancomycin overexposure. An inaccuracy of CL Cr estimates was encountered whenever the daily output of creatinine from muscles is impaired by the degree of muscle loss which may occur when a patient is bedridden for a long time (9,11). Another limitation may be represented by the fact that these nomograms are not valid for functionally anephric patients on dialysis and perhaps also for patients with very low CL Cr estimates of Ͻ10 ml/min.…”
Section: Discussionmentioning
confidence: 99%
“…Although plasma creatinine concentration is frequently used to quantify renal function and the severity of renal impairment, it can be difficult to interpret in patients with unstable renal function (17). Two-, four-and six-hour creatinine clearance (CrCl) have, however, been shown to closely correlate with 24-hour CrCl for diagnosis of AKI (18,19).…”
Section: Study Protocolmentioning
confidence: 99%
“…It is acknowledged that CL CR is not a 'gold standard' measure of glomerular filtration (such as inulin CL), albeit tubular CR secretion is unlikely to influence the result at higher filtration rates (213). Two-hour urinary collections were employed, as prior research has reported acceptable accuracy compared with longer time-periods (43). The implications of the proposed ARC scoring system are also acknowledged, with the current findings being primarily speculative.…”
Section: Discussionmentioning
confidence: 99%
“…Although less readily obtainable in the ambulatory patient, urinary catheterisation is frequent in the critically ill, making a timed urinary collection relatively easy. The duration of collection can be anywhere from 2 to 24hours (43,(55)(56)(57)(58)(59), with reasonable correlation between results (43). Eight-hour collections appear to provide the best balance between accuracy and feasibility (45), and can usually be reported daily, allowing the clinician to monitor trends and tailor therapy accordingly.…”
Section: Identifying Arc Using Established Measures Of Renal Functionmentioning
confidence: 96%
See 1 more Smart Citation